Measuring Stereotype Threat at Math and Language Arts in Secondary School: Validation of a Questionnaire - Bedyńska, Sylwia; Rycielski, Piotr; Jabłońska, Magdalena (Frontiers in Psychology, 2021)
A stereotype threat arises when a negative stereotype about group to which an individual belongs is activated. It affects the achievement and interest of students in a particular academic domain, e.g., girls at math or boys at language arts. Hence, it is important to assess the level of stereotype threat at school (STaS) in order to identify the vulnerability of students to its negative consequences. This study devised and validated two parallel versions of the STaS scale: girls in mathematics and boys in language arts in a nationally representative sample of Polish secondary school students (N = 1,241; 13–16 years). The results of a confirmatory factor analysis (CFA) in a complex sample approach showed one general factor. Furthermore, a multiple-group CFA confirmed metric invariance and partial scalar invariance. The variances for boys and girls were equal. This suggests that the construct of stereotype threat is similarly conceptualized by both genders despite being in different domains. Finally, the comparison of means of latent variables revealed a higher level of stereotype threat among boys in the language domain than girls in mathematics. Possible theoretical and practical implications are discussed.